Establishment of a Novel Mouse Hepatocellular Carcinoma Model for Dynamic Monitoring of Tumor Development by Bioluminescence Imaging - Cao, Xiangyi; Zhang, Yulong; Zhou, Qianqian; Sun, Sujing; He, Minwei; Wang, Xiaohui; Ma, Ping; Yang, Xiaoang; Lv, Liping; Zhan, Linsheng (Frontiers in Oncology, 2022)
We established a novel mouse model of hepatocellular carcinoma (HCC) model by simultaneously knocking out Pten and p53 suppressor genes and overexpressing the C-Met and △90-β-Catenin proto-oncogenes in mouse liver via hydrodynamic injection (HDI). The mutations were introduced using the CRISPR/Cas9 and Sleeping Beauty transposon systems. In this way, we rapidly established a primary liver cancer model within six weeks. In addition, we engineered macrophages expressing arginase-1 promoter coupled with firefly luciferase for bioluminescence imaging (BLI) of the tumor microenvironment. This novel, rapidly generated model of primary hepatocellular carcinoma can be monitored noninvasively which is conducive to further application of the model, helping to develop new drugs and treatment strategies of HCC.